Model Dan Strategi Pendidikan Nilai Pada Pendidikan Dasar, Menengah Dan Pendidikan Tinggi - Aris Saputro (LPPM Universitas PGRI Adi Buana Surabaya, 2020)
The purpose of writing this article is to understand the model and strategy of value education in primary, secondary, and higher education. Education is one of the fundamental things every human being needs. The result of the discussion of value education models and strategies is that value education is an effort to establish the personal attitudes of students that makes increasingly sincere with the system of value disclosure techniques, moral cognitive development models, value analysis models, and social action models as well as some strategies that make individual personality understated. The conclusion that the model and strategy of value education in primary, secondary, and higher education can develop humanist values.